The child in the electric chair : the execution of George Junius Stinney Jr. and the making of a tragedy in the American South - Faber, Eli, 1943-2020 (University of South Carolina Press, 2021)
"Eli Faber, professor of history emeritus, John Jay College of Criminal Justice, has written a narrative history of the case of George Stinney, a fourteen-year-old African American boy who was executed for the alleged murder of two white girls (ages 8 and 11) in June 1944. This made Stinney the youngest person executed in the United States in the 20th century. In 2014, a circuit court judge in South Carolina vacated the conviction. Faber moves beyond the single horrific moment to give a fuller picture of Stinney's world, attempting to answer the question, 'How was it possible, even for a state in the Deep South like South Carolina, to send a fourteen-year-old child to the electric chair in the middle of the twentieth century?' While the Stinney case has received periodic attention in the popular press, especially around the time of the vacated conviction, Faber's work represents the first extended, scholarly treatment of the case, its context, and its legacy. One reason for the lack of extended attention is the fact that no trial transcript exists (indeed, the trial itself lasted only 10 minutes). Faber makes use of traditional newspaper and archival sources in order to build the context necessary for understanding the events that led to Stinney's execution. Of note is a hitherto untapped collection of oral interviews conducted with observers and participants in 1983. The Stinney case, and even more its context and legacy, remain of vital importance today. The story that Faber tells is one of how a systemically racist system, paired with the personal ambitions of powerful individuals, combined to sacrifice the life of an African American child in order to support the maintenance of that system ... The ability to place the Stinney case into a larger context is the most significant contribution that Faber provides and he effectively shows how this case is not just a travesty of justice that is locked in the past, but rather one that continues to resonate in our own time ... [Faber] does more than ... [the] journalistic accounts to understand the events of 1944 as operating within a racial caste system, one evident not only in the trial itself but also the landscape and power structures of the town and the state..."--